Fate and Fortune in European Thought, ca. 1400-1650
1 online resource.
Keywords: If the universe were conceived to fulfill a certain divine plan or to manifest God's will and glory, what would the place of an individual be within this plan? What is more, if, from the very beginning of its existence and through divine providence, it were predestined to be driven toward a certain end, how could people adjust their individual lives to the incognizable universal design and react to the obscure future fraught with both luck and failure? These questions, which have bothered humanity for centuries, formed a remarkable element of early modern European thought. This collection of essays presents new insights into what shaped and constituted reflections on fate and fortune between, roughly, 1400 and 1650, both in word and image. This volume argues that these ideas were emblematic of a more fundamental argument about the self, society, and the universe and shows that their influence was more widespread, geographically and thematically, than hitherto assumed. Contributors are: Damiano Acciarino, Ovanes Akopyan, Elisabeth Blum, Paul Richard Blum, Jo Coture, Guido Giglioni, Dalia Judovitz, Sophie Raux, Orlando Reade, and John Sellars.